Apparatus and method for measuring flow rate of fluid - Shafie, Suhaidi; Garmabdari, Rasoul; Mohd. Isa, Maryam (2013)
The present invention relates to an apparatus and method for measuring flow rate, instantaneous consumption, and periodical consumption of fluid using Hall-effect sensors. The apparatus comprises a rotating disc (100) and a plate (101). The rotating disc (100) is coupled to a shaft (100a) having magnets (100b) and balance weights (100c) embedded on the surface or within the body. The shaft (100a) is coupled to a turbine (300) or a set of mechanical gears (300a). It is preferred that the magnets (100b) are alternately positioned with the balance weights (100c). A plurality of complementary sensor groups (101a) is disposed on the plate (101) and configured to be in communication with the magnets (100b) so as to provide one or more output signals representative of a rotational velocity of the rotating disc (100). Preferably, each of the complementary sensor groups (101a) comprises one or more Hall-effect sensors.